A Mouse Model of MC903‐Induced Atopic Dermatitis. Issue 3 (13th March 2023) - Alam, Md Jahangir; Xie, Liang; Yap, Yu‐Anne; Robert, Remy
Abstract: Atopic dermatitis (AD) is a chronic, relapsing, and extremely pruritic inflammatory skin disease with a particular impact on children. AD pathogenesis is not yet fully understood, and there is no curative treatment for this disease. Therefore, several genetically or chemically‐induced AD mouse models have been developed. These preclinical mouse models are an indispensable research tool for studying AD pathogenesis and evaluating the efficacy of new candidate AD therapeutics. A commonly used mouse model of AD has been developed using the topical application of a low‐calcemic analog of vitamin D3, MC903, to induce AD‐like inflammatory phenotypes that closely resemble human AD. Moreover, this model shows a minimal effect on systemic calcium metabolism that is observed in the vitamin D3‐induced AD model. Thus, an expanding number of studies use the MC903‐induced AD model to interrogate AD pathobiology in vivo and to test new candidate small molecule and monoclonal antibody therapies. This protocol describes in detail functional measurements including the measurement of skin thickness, which is a surrogate marker for ear skin inflammation, as well as itch assessment, histological evaluation to assess the structural changes associated with AD skin inflammation, and preparation of single‐cell suspensions from ear skin and draining lymph nodes for the assessment of inflammatory leukocyte subset infiltration in these tissues using flow cytometry. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Topical application of MC903 induces AD‐like skin inflammation Support Protocol 1 : Measurement of ear skin thickness Support Protocol 2 : Itch assessment Support Protocol 3 : Dissection of ear skin and ear draining lymph nodes Support Protocol 4 : Histological evaluation and quantification Support Protocol 5 : Preparation of single‐cell suspension from ear skin and draining lymph nodes for the assessment of inflammatory immune cell infiltration using flow cytometry